New developments in the management of schizophrenia and bipolar disorder: potential use of cariprazine - Werner FM; Coveñas R (Dove Medical Press, 2015)
Felix-Martin Werner,1,2 Rafael Coveñas2 1Euro Akademie Pößneck, Higher Vocational School for Elderly Care and Occupational Therapy, Pößneck, Germany; 2Institute of Neurosciences of Castilla y León (INCYL), Laboratory of Neuroanatomy of the Peptidergic Systems (Lab. 14), University of Salamanca, Salamanca, Spain Abstract: Cariprazine is a recently developed antipsychotic drug with a partial agonism for the D2 and D3 receptors. It shows a tenfold greater affinity for the D3 receptor. In clinical trials, its therapeutic effect has been tested in patients with an acute exacerbation of schizophrenia and in patients with acute mania in bipolar disorder. Like risperidone, cariprazine improves positive and negative schizophrenic symptoms, and ameliorates cognitive functions. Cariprazine induces extrapyramidal symptoms less often than risperidone and can cause acute akathisia. It is a prolactin-sparing antipsychotic drug and has a favorable metabolic profile. In acute mania in bipolar disorder, it treats manic symptoms significantly better than placebo. As a consequence of its improved adverse effects, cariprazine improves patients’ quality of life to a greater extent than other second-generation antipsychotic drugs. Cariprazine is a promising antipsychotic drug in the treatment of schizophrenia, acute mania in bipolar disorder, and in schizophrenia with mania. In these patients, its long-term therapeutic effect and its action in comparison with other second-generation antipsychotic drugs, above all aripiprazole, remain to be tested in clinical trials. Keywords: cariprazine, second-generation antipsychotic drug, schizophrenia, acute mania, D2 receptor, D3 receptor, partial agonism, akathisia, metabolic parameters, cognitive function